Profil Kebugaran Jasmani Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Subang - Deni Mudian; Arif Fajar Prasetiyo (Concept: Journal of Social Humanities and Education, 2024)
Students' physical fitness conditions can be developed to the maximum so that they can achieve maximum academic achievement. But in reality, many students ignore a healthy lifestyle, such as staying up late and other negative activities. This usually results in a decline in the quality of students' physical fitness, making it difficult to achieve optimal academic performance. This research aims to obtain a clear picture of the level of physical fitness of students at the Faculty of Teacher Training and Education, Subang University. The research method used is a descriptive method. The research subjects were 70 FKIP University Subang students. The research instrument was a physical fitness test observation sheet. In this study, five components of physical fitness were examined, including sprinting 60 meters, push ups, sit ups, vertical jumps, and middle distance running 1200 meters. The results of the research show that the overall physical fitness condition of Subang University FKIP students is in the poor category.